New Way to Develop the Patient Care in DM Clinic by the Patient Network - Tanasaeri, Sarawut (Journal of Health Science of Thailand, 2018)
Diabetic mellitus is a common chronic disease and costly for the continuing care of the DM patients, for example, stroke, coronary heart disease, renal failure, cataract and diabetic foot. The quasi-experimental study was to evaluate the patient care system with the newly established network in reducing the rate of loss follow up and improvment of blood sugar level in diabetic clinic relative to the former practice It was found that the DM clinic with the patient network could reduce the loss follow up rate and decrease the mean blood sugar level in DM clinic. Acute complications were hence visibly reduced leaving out long term complications to be followed up in a long run. It was summarized that DM clinic is necessary and should be replicated in other areas.